Population growth and housing demand in greater Abidjan, Ivory Coast - DEKI, Kouakou Tehua Pierre; DANVIDE, T. Bénoît; ZINSOU-KLASSOU, Kossiwa; MARTOS, Juan Carlos MAROTO (Edelweiss Applied Science and Technology, 2025)
African cities are experiencing population growth. This growth results from both natural movements and migration. The city of Abidjan is a prime migration hub given the economic opportunities it offers. This urban growth generates a strong demand for housing in the city. The objective of this article is to highlight the difficulties in accessing housing resulting from Abidjan’s urban dynamics. Using a methodology that combines qualitative and quantitative aspects, we interviewed 200 households and 50 real estate developers in four municipalities of Greater Abidjan. We found that the housing supply in Abidjan is lower than the demand. Furthermore, housing has experienced speculation over the years; homeowners also impose excessive conditions that limit access to housing in the city. This study involves actions to improve housing conditions in Greater Abidjan. First, on a political level, it is up to the state to see its social housing projects through to completion to avoid unfinished projects. The state can also make the cost of building materials affordable for middle-income populations. Granting lease loans to the population can help eradicate this situation. It is also necessary to encourage donors to invest in the city, which is another action the state should consider.